Pest status, bio-ecology and management of the false codling moth, Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) and its implication for international trade. Issue 1 (17th February 2021) - Adom, M.; Fening, K. O.; Billah, M. K.; Wilson, D. D.; Hevi, W.; Clottey, V. A.; Ansah-Amprofi, F.; Bruce, A. Y.
Abstract: The false codling moth (FCM), Thaumatotibia leucotreta (Lepidoptera: Tortricidae) is an insect pest which represents an important threat to the production and marketing of a wide range of agricultural crops in the African-Caribbean-Pacific (ACP) countries. The FCM reduces not only the yield and quality of the crop but also as a quarantine insect pest, restricts the trade of susceptible agricultural produce on the international market. In addition, little research has been conducted in the ACP countries on the bio-ecology and sustainable management of this pest, especially on vegetables for export. Thus, action-oriented research aimed at understanding the bio-ecology of this important pest is essential to achieve effective management. Various management interventions against this pest have been used in some parts of the world, especially in South Africa on citrus. Currently, farm sanitation is regarded as the key management strategy. Exploring and improving on other interventions such as Sterile Insect Technique, monitoring and mass trapping of male moths, augmentative biological control, use of bio-pesticides, protected cultivation and cold treatment may help to mitigate the expansion of FCM into other countries, especially in the European and Mediterranean Plant Protection Organization region where it has become a regulated insect pest since 2014. This review discussed the bio-ecology of FCM and highlighted some of the challenges and opportunities for its effective management and its implication for international trade, especially the export of chillies from the ACP countries into the European Union market which requires strict phytosanitary regulations.